1996
DOI: 10.1038/381800a0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ceramide-mediated programmed cell death by sphingosine-1-phosphate

Abstract: Ceramide is an important regulatory participant of programmed cell death (apoptosis) induced by tumour-necrosis factor (TNF)-alpha and Fas ligand, members of the TNF superfamily. Conversely, sphingosine and sphingosine-1-phosphate, which are metabolites of ceramide, induce mitogenesis and have been implicated as second messengers in cellular proliferation induced by platelet-derived growth factor and serum. Here we report that sphingosine-1-phosphate prevents the appearance of the key features of apoptosis, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
1,141
2
11

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,438 publications
(1,217 citation statements)
references
References 28 publications
49
1,141
2
11
Order By: Relevance
“…Recent ®ndings indicate an important role for ERKs in the protection of di erentiated PC12 cells from growth factor withdrawal (Xia et al, 1995) and ceramide-induced apoptosis (Cuvillier et al, 1996). We have previously reported that Gas6 induces a transient activation of ERK (Goruppi et al, 1996): we therefore analysed here the role of ERK in Gas6 survival signalling.…”
Section: Discussionmentioning
confidence: 97%
“…Recent ®ndings indicate an important role for ERKs in the protection of di erentiated PC12 cells from growth factor withdrawal (Xia et al, 1995) and ceramide-induced apoptosis (Cuvillier et al, 1996). We have previously reported that Gas6 induces a transient activation of ERK (Goruppi et al, 1996): we therefore analysed here the role of ERK in Gas6 survival signalling.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, it has been suggested that S1P may be a potent neuroprotective factor against Aβ-induced neuronal apoptosis, and that it that acts by inhibiting ASM activation (GomezMunoz et al, 2003;Malaplate-Armand et al, 2006). Thus, during the past decade a model has been proposed in which the balance between the levels of ceramide and S1P, the 'ceramide/S1P rheostat', contributes to the fate of cells (Cuvillier et al, 1996). Based on this model, the regulation of sphingomyelinases and ceramidases, as well as sphingosine kinase, S1P phosphatase and lysase may play pivotal roles in the apoptotic signaling of cells by regulating the ratio between sphingomyelin, ceramide, sphingosine, and S1P.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition and/or downregulation of PKC has been shown previously in many studies to induce apoptosis in many cell types although many of these studies su er from the use of compounds which inhibit other kinases in addition to PKC (reviewed by Dive et al, 1992a). More recently activation of PKC has been shown to suppress ceramide induced apoptosis (Cuvillier et al, 1996), and from our own studies appears to be important for v-Abl mediated suppression of apoptosis induced by cytokine deprivation and exposure to anticancer drugs (Evans et al, 1995;Chapman et al, 1995). The activity of PKC may either lead to regulation of Bcl-2 and Bclx L via e ects on transcription, and/or may a ect their function via posttranslational modi®cation.…”
mentioning
confidence: 89%